PALEOMAGNETIC AND PALYNOLOGIC INVESTIGATIONS IN THE UPPER VALDARNO BASIN (CENTRAL ITALY): CALIBRATION OF AN EARLY VILLAFRANCHIAN FAUNA (Rivista italiana di Paleontologia e Stratigrafia, 1997)
The silty clays embedding an early Villafranchian mammal fauna of the Triversa faunal unit (f.u.) have been paleomagnetically and palynologically studied in a continuous sequence exposed in the Santa Barbara quarry.The study has allowed to date the earliest occurrence in Italy of a faunal assemblage of this unit and to define the corresponding climatic conditions. The sampled section has provided a magnetic polarity sequence of the late Gauss,where the fossiliferous layer fits the Kaena reversed interval.Its age of ca. 3.1 Ma,during subtropical climate conditions correlatable to the Reuverian of Netherlands, suggests an older age for the beginning of the Villafranchian, possibly associated to a more dramatic scenario able to trigger the faunal turnover.